Formulation and Optimization of Oral Fast Dissolving - Dua'a K. Ahmed; Balkis A. Kamal (College of Pharmacy University of Baghdad, 2017)
Prochloperazine maleate (PCM) is one of the most prescribed phenothiazine. The purpose of the present research was to develop fast dissolving tablets of PCM with Î²-cyclodextrin inclusion complex. Tablets prepared  by wet granulation with sublimation and by using  different superdisintegrants type [ low-hydroxypropylcellulose LH21 (L-HPC LH21), carboxymethylcellulose calcium (ECG505), crospovidone (CP)], and different type of subliming agents (urea and ammonium bicarbonate (AB)). Tablets evaluated for its % friability, disintegration time, wetting time, hardness, content uniformity, weight variation, in vitro dissolution studies. For further enhancement of disintegration and dissolution, PCM orodispersible tablet were formulated as (PF2,PF3 and PF4) using inclusion complex of drug in Î²-cyclodextrin at  different ratios (1:1, 1:2 and 1:3) respectively. These formulation showed disintegration times between (22s and 14.6s), and drug release showed t80% between (2.9% and 0.9%). Among all the formulations PF4 was considered as the best, containing PCM: Î²-cyclodextrin 1:3, 10% crospovidone and 25% ammonium bicarbonate which shows the shortest DT, good dissolution study and stability. The overall results suggest that the orodispersible tablet of PCM enhance the absorbable part than that of corresponding conventional tablet  by using superdisintegrants and Î²-cyclodextrin inclusion complex of drug. Key words: Prochloperazine maleate, Orodispersible tablet, Crospovidone, Ammonium Bicarbonate, Sublimation.